A lima bean core collection based on molecular markers - Gomes, Regina Lucia Ferreira (2020)
Some germplasm collections have a high number of accessions, which makes it difficult to explore the genetic variability present in the germplasm bank due to the redundancy and the difficulty of detailed analysis of all conserved accessions. Therefore, our study aimed to analyze the genetic diversity of 153 lima bean (Phaseolus lunatus) accessions for the purpose of constructing a core collection. Eleven SSRs were used for this purpose. The 153 lima bean accessions can be represented by low redundancy using a minimum of 34 accessions, thus representing 22 % of the size of the entire germplasm bank. The core collection had a higher Shannon diversity index and expected heterozygosity (1.906 and 0.811, respectively) than those presented by the entire germplasm bank (1.605 and 0.713, respectively), indicating a higher polymorphism of the representative cultivars in relation to the entire collection. The accessions selected for the core collection may be used in future studies of genome association as well as in genetic crosses in breeding programs aimed at developing improved cultivars with high genetic diversity which can meet current and future market needs.